Building a knowledge and learning society in Portugal - Adult students in technological schools and higher education institutions - Correia, Ana Maria R (2009)
Chapter in Merrill, Barbara (ed.) (2009) Learning to Change? The Role of Identity and Learning Careers in Adult Education. Hamburg: Peter Lang Publishers. URL: http://www.peterlang.com/ index.cfm?vID=58279&vLang=E&vHR=1&vUR=2&vUUR=1